SMART CITY POLICY BETWEEN INSTITUTIONS AND CITIZENS: THE PERSPECTIVE OF THE CITY OF MILAN - Melchionda, Mariano (Economy and Sociology, 2024)
In the environmental and climate issue, a decisive role is played by mobility. In recent years we are witnessing a kind of transportation revolution, especially urban transportation, with a sustainable mobility. It is today one of the many aspects in which cities need to renew themselves, thus facilitating their transition to the smart city dimension. The smart city represents the latest trend in urban planning aimed at improving the quality of life. It is now widely talked about: in politics, for example, the concept is used to illustrate new urban development strategies aimed at improving the architecture, mobility and infrastructure of metropolises. However, although the idea of a smart city is based on the use of modern technologies, it is considered "smart" when it innovatively manages its economic and environmental resources, housing and transportation policies, relations and methods of administration. Smart cities focus on environmentally and sustainable urban development, using technology to reduce pollution or generate alternative energy. The study therefore aims to analyze how a smart city develops and what are the main actors and elements that play a key role in the analysis of the topic: institutions and citizens. By harnessing information communication technology and improving local infrastructures and transports, the institutions of the city of Milan proactively monitored city dynamics, drove positive changes, and enhanced residents’ quality of life. This enabled direct engagement with both residents and infrastructure, making Milan one of the most cutting-edge cities not only in Italy, but also in the international context.